Work satisfaction among rank and file police personnel of Royal Malaysia Police - Mohd Othman, Fazilah; Hanafi, Nurshafizah; Mustafa Kamil, Bidayatul Akmal; Teh, Ming Tat (2020)
Community empowerment is an effort or process to raise awareness, willingness, and the ability of the community to recognize, overcome, maintain, protect, and improve their welfare. One of the ways to realize community empowerment can be implemented is through a group of people who want to participate in it. This is one solution for farmers to be more effective in developments in agriculture. The research method used in this research is descriptive qualitative research method. The analysis technique in this study uses qualitative analysis techniques by revealing facts of circumstances, phenomena, variables, and circumstances that occur when the research is running and presenting the real facts and concluding. The result of the research is an analysis of partnership activities with the community in the form of farming activities in the agricultural sector to the marketing of agricultural products whose final goal is to increase food security. Besides, this partnership program also produces a legal farmer group with the name "Maju Mapan" which is a legal entity. Through community empowerment, especially the residents of Kampung Wak lolang Tanjung Moco, it appears that in the context of increasing food security, community empowerment activities based on partnerships in agriculture can be carried out.